ASSOCIATION BETWEEN DOMINANT TREES SPECIES IN LOWLAND TROPICAL FOREST (EDUCATION FOREST OF JAMBI UNIVERSITY) - Nursanti Nursanti; Rizky Ayu Hardiyanti; Ade Adriadi (Media Konservasi, 2021)
Lowland forest vegetation can still be found on the Jambi University Campus, namely at the Jambi Mendalo University Educational Forest (HPUJM). Jambi University Educational Forest is administratively located in Mendalo Indah Village, Jambi Luar Kota District, Muaro Jambi Regency, Jambi Province. Vegetation communities are formed by the presence and interaction of the various types of plants that compose them. The form of interaction between plant species in a community is called an association. Associations can be in the form of positive associations and negative associations. This research was conducted to know the association between dominant tree species. This study used a purposive sampling method by determining a sampling area of ​​9600 m2 or 0.96 ha measuring 160m x 60m, divided into 24 sub-plots, each measuring 20m x 20m. Species having an Importance Value Index (IVI) of ≥ 10% were used as the association analysis. The 2x2 contingency table was used to analyze whether or not associations were present between tree species. The results showed, of 15 dominant tree combinations, there were only 4 associated combinations, namely the association between Aporosa lucida and Vitex pinnata, the association between Endospermum diadenum and V.pinnata, the association of Litsea ferruginea with Gironniera diadenum, the association of L. ferruginea with V.pinnata. Key words: association, dominant tree, lowland forest